SOCIOLOGICAL STUDY REGARDING THE FEMALE ADOLESCENTS' PERCEPTION OF THE EFFECTIVENESS OF AEROBIC GYMNASTICS - Dumitru R.C; Dobrescu T.; Zaharia A.M (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2012)
Aerobic gymnastics is addressed in equal measure to women and men, to young and old people, the reason for its accessible nature being the harmoniously combination between simple exercises and dance elements. Starting from this premise, this research verifies the female students' knowledge regarding aerobic gymnastics as an alternative for a healty lifestyle. The main goal of this study was to identify how much the non-Physical Education female students are aware of the effects the aerobic gymnastics has on the body, and at the same time, to identify their motivation for this option. The research was conducted on a target group comprised of female students between 19 and 25 years old, at the "Vasile Alecsandri" University of Bacău, specializing in non-Physical Education disciplines. The questionnaire comprised 10 items with open, and prefigured answers. At the end of the inquiry, we observed a considerable number of respondents who chose to practice aerobic gymnastics, manifesting a favorable attitude towards movement. We also observed a large number of students identifying the beneficial influences of aerobic gymnastics and its role in maintaining your energy and strength, increasing the stamina, the state of well-being (mental relaxation), choosing a new, healthy lifestyle.